Implementation of a damage model in a finite element program for computation of structures under dynamic loading - Nasserdine Oudni; Youcef Bouafia (Fracture and Structural Integrity)
This work is a numerical simulation of nonlinear problems of the damage process and fracture of quasi-brittle materials especially concrete. In this study, we model the macroscopic behavior of concrete material, taking into account the phenomenon of damage. J. Mazars model whose principle is based on damage mechanics has been implemented in a finite element program written Fortran 90, it takes into account the dissymmetry of concrete behavior in tension and in compression, this model takes into account the cracking tensile and rupture in compression. It is a model that is commonly used for static and pseudo-static systems, but in this work, it was used in the dynamic case.